2002
DOI: 10.1111/j.1549-0831.2002.tb00118.x
|View full text |Cite
|
Sign up to set email alerts
|

Poor People in Poor Places: Local Opportunity Structures and Household Poverty*

Abstract: Accounts of poverty generally fall into either “individualist” or “structuralist” camps. Often these are seen as irreconcilable and incompatible competing perspectives. This paper integrates individualist and structuralist accounts of poverty by examining the relationship between “person poverty” and “place poverty” in nonmetropolitan and metropolitan labor markets, using a multilevel framework. I fashion a general model of poverty production and allocation, drawing on the labor market ecology perspective. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
6

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 27 publications
2
83
1
6
Order By: Relevance
“…This is due in part to the fact that agriculture tends to predominate in rural areas with less diversified economies, and is also characterized by particularly high rates of underemployment compared to other industries (Slack and Jensen 2004). Research has also found the percentage of the working age population that is employed (versus unemployed or not in the labor force) is negatively associated with poverty (Cotter 2002;Gunderson 2006). This stands to reason since employment tends to be the strategy by which most non-wealthy Americans earn a living.…”
Section: Employment Structurementioning
confidence: 91%
See 2 more Smart Citations
“…This is due in part to the fact that agriculture tends to predominate in rural areas with less diversified economies, and is also characterized by particularly high rates of underemployment compared to other industries (Slack and Jensen 2004). Research has also found the percentage of the working age population that is employed (versus unemployed or not in the labor force) is negatively associated with poverty (Cotter 2002;Gunderson 2006). This stands to reason since employment tends to be the strategy by which most non-wealthy Americans earn a living.…”
Section: Employment Structurementioning
confidence: 91%
“…Research has found that migrants are drawn to areas with stronger job opportunities (Frey and Liaw 2005), while areas people are leaving tend to be associated with higher poverty rates (Rupasingha and Goetz 2007). Age structure has also been shown to be an important correlate of poverty, with places characterized by a younger age structure tending to have higher levels of poverty (Cotter 2002;Rupasingha and Goetz 2007) due to the aforementioned economic disadvantages faced by children. Immigration is another factor that influences poverty.…”
Section: Population Structurementioning
confidence: 99%
See 1 more Smart Citation
“…As such, they blur the artificial boundaries between micro and macro analyses. Many examples of multilevel modeling can be found in the sociological and demographic research beginning in the 1980s (e.g., Cotter 2002;Hirschman and Guest 1990;DiPrete and Grusky 1990;Sampson 1988Sampson , 1991Sampson and Wooldredge 1987;Raudenbush and Bryk 1986;Entwisle et al 1984, 1986Entwisle and Mason 1985Mason et al 1983Mason et al -1984. Comparable to the experience with spatial econometric modeling, technological advances in software capabilities have greatly facilitated an already existing interest in hierarchical data analysis.…”
Section: Multilevel Modelingmentioning
confidence: 98%
“…Perspektiva "koncentrovaného znevýhodnění", využitá explicitně i v české analýze vnitřních periferií [Musil, Müller 2008a], přitom není zcela oddělena od pojetí periferií jako nejslab-ší části ekonomicky polarizovaného území. Jejich styčné body vycházejí z před-pokladu, že ekonomická izolace a závislost lokality má výrazný vliv na životní podmínky jejích obyvatel, na problematizaci jejich postavení na trhu práce, na ná-růst chudoby a sociálního vyloučení a na snižování kvality života [Cotter 2002].…”
Section: Teorie Deprivaceunclassified